EFFECT OF STIMULATION OF SENSORY NERVES UPON THE RATE OF LIBERATION OF EPINEPHRIN FROM THE ADRENALS - Stewart, G. N. (The Rockefeller University Press, 1917)
An attempt was made to determine whether stimulation of afferent nerves (sciatic and brachial) produced a detectable increase in the rate of liberation of epinephrin from the adrenals, as determined by testing adrenal vein blood on rabbit intestine and uterus segments. The result was negative.